Analysis of Post-COVID Hajj Fund Investment Strategy in Indonesia - Irkham Karunia Aji; Anis Chariri (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the post-COVID investment strategy implemented by the Hajj Financial Management Agency (Badan Pengelola Keuangan Haji/BPKH) in Indonesia. The COVID-19 pandemic has significantly disrupted global financial systems, affecting Hajj fund management, liquidity, and return stability. BPKH responded by strengthening its governance, focusing on prudence, sharia compliance, and adaptive diversification. This research employs a qualitative approach with a case study design, utilizing interviews and document analysis to examine strategic shifts in investment management. Findings reveal that BPKH’s investment strategy is guided by Dynamic Capabilities Theory, emphasizing sensing, seizing, and transforming capabilities. Post-pandemic strategies include increased allocation to State Sharia Securities (SBSN), portfolio diversification, risk management reinforcement, and enhanced digitalization. Effectiveness is measured through benefit value growth, liquidity fulfillment, and sharia compliance. BPKH achieved 101.02% of its benefit value target in 2024, reflecting stable performance despite global volatility. This study concludes that BPKH’s conservative yet adaptive approach effectively sustains Hajj fund growth, while further diversification into global sharia instruments and ESG sukuk is recommended for future resilience